The role of background factors for reading literacy: straight national scores in the PISA 2000 study - Fertig, Michael; Schmidt, Christoph M. (Discussion paper series, 2002)
Based on the individual-level data of the PISA 2000 study, this note provides a detailed econometric analysis of the way that reading test scores are associated with individual and family background information and with characteristics of the school and class of the 15 to 16 year old respondents to the survey. Based on our quantile regressions, we interpret the national performance scores conditional on these observable characteristics, as the reflection of different education systems. Our findings suggest that US students, particularly those in the lower quantiles, are served relatively unsatisfactorily by their system of education. Moreover, part of the potential for improvement seems to involve measurable aspects which could be altered and monitored easily.
Keywords: Arbeitspapier; Graue Literatur